Pedagogical management in times of crisis: a dynamic thought from interdisciplinary practice: Pedagogical management in times of crisis: a dynamic thought from interdisciplinary practice - BARBERA ALVARADO, Nataliya; CHIRINOS ARAQUE, Yamarú; VEGA MARTINEZ, Arney; HERNANDEZ BUELVAS, Efrain (Utopía y Praxis Latinoamericana, 2021)
This article aims to characterize pedagogical management from the interdisciplinary practice of the teacher in the face of the emergence of covid-19. It is a quantitative research with a descriptive - transectional scope. The results allowed to conclude that, in these times of crisis, pedagogical management assumes a strategic governance approach by establishing lines of action that favor synchronous relationships between teachers - students - community to efficiently and effectively develop academic, administrative and social activities, as well as, face challenging, uncertain and unthinkable circumstances through technological platforms. It is an interdisciplinary, integrated, constructive and contextualized practice that is based on linguistic mediation to promote collaborative work between educational, institutional and / or community actors.